Analysis of the Use of Social Media Advertising on Sabila Craft Sales Using the AISAS Method - harahap, widiya lestari (Titik Imaji, 2025)
In the rapidly evolving digital era, social media has become the main platform in marketing for businesses of all sizes, including small and medium-sized businesses. Sabila Craft, a creative venture that focuses on delivery design products and acrylic prints, leverages social media to increase reach and attract customers. Despite having gained recognition for the quality and unique design of its products, Sabila Craft faces challenges in local market competition and limited marketing budgets. Therefore, this study analyzes the implementation of the AISAS (Attention, Interest, Search, Action, Share) model in Sabila Craft's social media strategy, in order to understand its impact on consumer purchasing decisions and increased sales. The AISAS model, which is designed to understand digital consumer behavior, has proven effective in helping Sabila Craft optimize customer interactions, increase interest, and leverage word-of-mouth effects to expand market reach. These findings are expected to be beneficial for small businesses in maximizing the potential of social media for sustainable growth